1905
DOI: 10.1093/brain/28.2.116
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Injury to the Peripheral Nerves in Man

Abstract: § 1.-Loss of Sensation after Division of the Ulnar Nerve. § 2.-Variation in the Extent of the Area supplied exclusively by the Ulnar Nerve. § 3.-Loss of Sensation after Division of the Ulnar Nerve when its Dorsal Branch remains Intact. § 4.-Loss of Sensation after Division of the Median Nerve. § 5.-Variation in the Extent of the Area supplied exclusively by the Median Nerve. § 6.-Loss of Sensation after Division of both'Median and Ulnar Nerves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

1916
1916
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Systemic factors include old age, malnutrition, fever, and severe illness (i.e., mumps, acute febrile tuberculosis, typhoid and chronic nephrosis) (37)(38)(39)(40). Local factors include denervation, including median or ulnar nerve injury (41,42), nail bed injury (43), nail matrix injury (44), sympathetic dystrophy (45), relapsing polychondritis (46), and local infection. Some chemotherapeutic or immunosuppressive agents, such as methotrexate and azathioprine, have also been reported (47) to decrease nail growth.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic factors include old age, malnutrition, fever, and severe illness (i.e., mumps, acute febrile tuberculosis, typhoid and chronic nephrosis) (37)(38)(39)(40). Local factors include denervation, including median or ulnar nerve injury (41,42), nail bed injury (43), nail matrix injury (44), sympathetic dystrophy (45), relapsing polychondritis (46), and local infection. Some chemotherapeutic or immunosuppressive agents, such as methotrexate and azathioprine, have also been reported (47) to decrease nail growth.…”
Section: Discussionmentioning
confidence: 99%
“…Head and Sherren (1905), however, believed that the slowing of growth observed in these cases wvas due entirely to the immobilization of the limb either as a result of splinting or paralysis and that division of sensory fibres without limitation of digital movements is not associated with any deficiency in nail growth. According to Bernhardt (1881) "nail growth is relatively independent of the influence of the nerve fibres innervating the fingers and tissues of the nail bed ", though his method of measuring growth from " the upper margin of the epidermis covering the nail root" was open to error.…”
mentioning
confidence: 91%
“…In 1903, Head persuaded his colleague, the surgeon James Sherren, to divide the superficial ramus of his own left radial nerve. After the operation he spent weekends at St. John’s College, Cambridge, where he and Rivers repeatedly mapped the sensory loss caused by the nerve section and the subsequent changes during regeneration [4, 5]. At first they observed that the vascular signs began to return to normal in 107 days and were quite normal in 190 days.…”
Section: Introductionmentioning
confidence: 99%